Compassion-focused group therapy improves depression, emotional eating, self-criticism and shame in people living with severe obesity: A single-centre, examiner-blind randomized controlled trial - Mary Hynes; Francis M. Finucane; Chris Collins; Timothy O’Brien; Oliver McAnena; Grace O’Shea; Monika Pilch; Brian E. McGuire (PLoS ONE, 2026)
Background Severe obesity (defined as a BMI ≥ 40 kg m -2 ) is often accompanied by significant mental health co-morbidities such as eating disorders and depressive disorder and people living with severe obesity often experience feelings of shame, self-criticism and feelings of inferiority in relation to others. Compassion Focused Therapy (CFT) was specifically designed for people with high levels of shame and self-criticism and aims to promote self-compassion which is regarded as an adaptive emotional regulation strategy. Aims To explore the effect on psychological outcomes of a 10-session (weekly for 2 hours) in-person, group-based CFT intervention for people living with severe obesity. We sought to determine whether CFT would lead to improved self-compassion, depressive symptoms, emotional eating, shame, self-criticism, submissive behavior, and negative social comparison. Method A single-centre, randomized controlled trial was carried out with 91 participants allocated to either ‘treatment as usual’ (n = 46) or ‘treatment as usual with additional group based CFT’ (n = 45). Treatment as usual included dietary advice, assessment by a Consultant Endocrinologist with possible prescription of medication, and participation in an eight-week lifestyle modification programme. Psychological outcomes were recorded at three time points (pre-treatment, post-treatment, and three-months after the end of group-based CFT). Results CFT led to statistically and clinically significant improvements in self-compassion, self-coldness, mood, shame, emotional eating, self-criticism, social comparison, and submissive behaviour (all p < 0.001) compared with treatment as usual. These results were maintained at three-month follow-up. Conclusions Group CFT appears to be an effective psychological intervention to alleviate psychological distress in people living with severe obesity. Trial registration ClinicalTrials.gov NCT03249441